Factors determining the types of beef cattle business in the counties of Mato Grosso do Sul - Pacheco, José Arlindo de Camargo; Costa, Fernando Paim (Pesquisa Agropecuaria Brasileira, 2014)
The parameters responsible for the beef cattle variation among the counties of the State of Mato Grosso do Sul were determined by using factor analysis applied over eight variables selected from the Agricultural Census of 1980. Two factors (F1 and F2) were the most important and explained 90% of the total variation. F1, responsible for 68% of the variation, is related to the beef production phasis (cow-calf, rearing or fattening) in association with the technological level. Explaining 21% of the variation, F2 means the degree in which the beef cattle is present at the county plus its technical efficiency. According to the scores of the factors the counties were grouped and for each factor the State of Mato Grosso do Sul was mapped.